Effect of immobilization parameters on the immobilization of cyclodextrin glucanotranferase on hollow fiber membrane - N., Jamil; Rohaida, Che Man; S., Suhaimi; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman (Penerbit Universiti Teknologi Malaysia, 2020)
Cyclodextrin (CD) is a non-reducing maltooligosaccharides which able to form inclusion complexes with many hydrophobic molecules, changing their physical and chemical properties. With these properties, CD has been discovered to have numerous applications in food industries, pharmaceutical, agricultural and environmental engineering. CD is produced by the enzymatic reaction between cyclodextrin glucanotransferase (CGTase) and starch. Various enzyme immobilization techniques such as adsorption, entrapment, encapsulation and cross-linking have been applied to improve the production of CD. Some of the immobilization parameters such as contact time, agitation rate and pH of the immobilization solution play a vital role in enzyme immobilization process, in order to achieve high production of CD. In the present study, the CGTase from Bacillus licheniformis was immobilized on polyvinylidene difluoride (PVDF) hollow fiber membrane via adsorption technique. The efficiency of enzyme immobilization appears to be affected by various factors (immobilization parameters) such as contact time, agitation rate and pH. Therefore, the effect of contact time (6-72 h), agitation rate (50-250 rpm) and pH (3-10) on the immobilization of CGTase on PVDF hollow fiber membrane were investigated in this study. The immobilized CGTase exhibited the highest immobilization yield of 69.37% under the conditions of 24 h contact time, 100 rpm and pH 7.0. Therefore, the influence of the immobilization parameters during the enzyme immobilization process is vital in order to achieve the high production of CD. Hence, high immobilization yield contributed to the high production of CD which in turn may be beneficial for the industrial purposes.